Progress in leptonic and semileptonic decays in lattice QCD - RYAN, SINEAD MARIE (American Physical Society, 1999)
The status of lattice calculations of heavy quark phenomenology is reviewed. Particular emphasis is placed on the understanding and control of the calculational uncertainties. The ensuing implications for constraining the CKM matrix elements are discussed.
PUBLISHED
Keywords: Pure & Applied Mathematics